2016
DOI: 10.1080/09602011.2016.1187630
|View full text |Cite
|
Sign up to set email alerts
|

A pilot investigation of the potential for incorporating lifelog technology into executive function rehabilitation for enhanced transfer of self-regulation skills to everyday life

Abstract: The objective of the study was to identify the potential target and effect size of goal management training (GMT) enhanced with life-logging technology compared with standard GMT on a range of possible primary outcomes reflecting cognitive and ecological aspects of executive functioning and quality of life. Sixteen patients with acquired brain injury involving executive dysfunction were randomly allocated to one of the two interventions: seven weeks of GMT (n = 8), or seven weeks of GMT+Lifelog (n = 8). Outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…One study used a sample of older women to examine physical activity and sedentary time [32]. No studies identified in our review recruited participants with a chronic disease; however one study including participants with an acquired brain injury [37]. The majority of studies included convenience samples, often recruited through universities, thus participants were more likely to be well-educated with higher socio-economic status.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study used a sample of older women to examine physical activity and sedentary time [32]. No studies identified in our review recruited participants with a chronic disease; however one study including participants with an acquired brain injury [37]. The majority of studies included convenience samples, often recruited through universities, thus participants were more likely to be well-educated with higher socio-economic status.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…The majority of the studies were conducted in the United States of America (n = 7, 29%) [22,25,27,29,31,32,36], the United Kingdom (n = 6, 25%) [9][10][11][12][13][14], and Ireland (n = 4, 13%) [24,30,33,35]. Three studies [23,26,28] were international multicentre studies, while the remaining studies were from New Zealand [8,20,34] and Spain [37].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relatively brief two-session goal management training adopted here (in comparison with the 14 or more hours of face-to-face GMT training typically reported 16 ) might be considered insufficient for many with ABI. Future evaluation of clinical effectiveness, should consider a more extended and tailored period of strategy and self-regulation training 16,17,22 and inclusion in the intervention of additional components that enhance likelihood of transfer of strategies 16,22,[41][42][43] .…”
Section: Generalizabilitymentioning
confidence: 99%